STABILITAS FISIK SEDIAAN LOTION O/W dan W/O EKSTRAK BUAH MAHKOTA DEWA SEBAGAI TABIR SURYA DAN UJI IRITASI PRIMER PADA KELINCI - Abdul Karim Zulkarnain; Meiroza Susanti; Aliva Nur Lathifa (Majalah Obat Tradisional, 2013)
Phalerin in extract of Phaleria macrocarpa fruit has activity as a sunscreen. The aims of this research was to discover the physical stability of extract in lotion  and primary irritation test. The optimal formulation o/w was determined by Simplex Lattice Design (LSD) method using software Design Expert® version 8.0.7 with variety of cetyl alcohol, stearic acid, and triethanolamine and lotion w/o with variety of cera alba, span 80 and cetyl alcohol. Lotion was made in 10 optimum formula then the physical characteristics were measured. The phycical characteristics was employed to create the optimum formula. The difference of physical characteristic between experimental and software was analyzed by one sample t-test analysis statistics. Optimum formula of lotion was determined on skin white rabbit. The optimum formula lotion o/w were cetyl alcohol 2,690%, stearic acid 4,146%, and triethanolamine 3,164% and lotion w/o were cera alba 12,136%; span 80 7,181%; and cetyl alkohol 3,683%. The result of one sample t-test gave no signifficant differences on physical characteristics between experimental and software. Optimum formula of lotion o/w was not irritant at topical on white rabbit skin.